2013
DOI: 10.5152/akd.2013.191
|View full text |Cite
|
Sign up to set email alerts
|

Impact of shisha smoking on the extent of coronary artery disease in patients referred for coronary angiography

Abstract: Objective: To study the impact of shisha smoking on the extent of coronary artery disease. Methods: Patients who underwent coronary angiography were included in this observational cohort study and were divided to four groups according to the smoking pattern: shisha smokers, cigarettes smokers, mixed smokers (shisha and cigarettes) and non-smokers. Coronary angiography was done and the severity of coronary artery disease was defined according to Duke Jeopardy Score (DJ). Results: The study comprised of 287 cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 15 publications
(20 reference statements)
1
35
0
Order By: Relevance
“… 24 Since then, more studies have evaluated this association including a cross-sectional study from Iran, 25 one prospective study 26 and one case–control study 27 from Bangladesh, 26 27 and three hospital-based cross-sectional studies from Lebanon, 28 Qatar 29 and Egypt. 30 Moreover, one community-based cross-sectional study from Jordan evaluated the association of WPS with hypertension. 31 …”
Section: Resultsmentioning
confidence: 99%
“… 24 Since then, more studies have evaluated this association including a cross-sectional study from Iran, 25 one prospective study 26 and one case–control study 27 from Bangladesh, 26 27 and three hospital-based cross-sectional studies from Lebanon, 28 Qatar 29 and Egypt. 30 Moreover, one community-based cross-sectional study from Jordan evaluated the association of WPS with hypertension. 31 …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, diabetic patients are known to have increased severity of atherosclerosis as well as higher rates for multivessel disease and more complex lesions such Comparison between intermediate SYNTAX score tertile and high SYNTAX score tertile; CVD -cerebrovascular disease; PAD -peripheral artery disease; WBC -white blood cell; LDL-C -low-density lipoprotein-cholesterol; HDL-C -high--density lipoprotein-cholesterol as long lesions, bifurcation lesions, and diffuse small vessel disease [16,17]. Furthermore, several studies have demonstrated that HT, smoking, and dyslipidaemia are associated with the complexity of atherosclerosis [18][19][20]. Also, Sunman et al [21] indicated that age, male gender, dyslipidaemia, and especially family history of premature CAD were associated with severity and extent of non-calcified coronary atherosclerotic plaques as shown by multidetector computed tomographic coronary angiography.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, shisha smokers with more than 40 years had three times more risk of having severe stenosis than non-smokers [29]. Shisha smoking was associated with severe coronary artery disease, which was dependent on the duration/frequency of shisha smoking [30].…”
Section: In Selim Et Al Study Smokers Of Both Shisha and Cigarettesmentioning
confidence: 97%